Depresi terhadap emotional eating yang memengaruhi status gizi lansia wanita di perdesaan - Wulan May Kusuma Dewi; Annisa Usfatun Khasanah; Salsa Ardyan Mustika Wati; Amilah Dwi Khusnul Qotimah; Luthfia Cahyadina Marjuki; Emy Huriyati (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada, 2026)
The effects of depression on emotional eating and nutritional status among elderly women in rural areasBackground: indonesia has entered an era of an aging population, with elderly women dominating and being vulnerable to malnutrition and depression, especially in rural areas such as Purwobinangun, Sleman. Depression in elderly women has a higher prevalence and impacts physical health, quality of life, and eating behavior through emotional eating mechanisms that can affect nutritional status.Objective: This study aims to determine the effect of depression on emotional eating on the nutritional status of elderly women in rural areas.Methods: The study design was cross-sectional and used the STROBE reporting guidelines. There were 140 elderly women respondents aged ≥60 years in Purwobinangun village, Sleman. Data were collected through interviews and measurements using sociodemographic forms, the GDS-15 questionnaire, DEBQ-EE, and MNA-SF. Linear regression analysis was the method used for path analysis, as well as the Sobel test.Results: Depression has a significant positive effect on emotional eating (?=0.184; p<0.05); depression has a significant negative effect on nutritional status (?=-0.288; p<0.05); and emotional eating has a significant negative effect on nutritional status (?=-0.19; p<0.05). However, the contribution of these effects is weak based on the R² value. There is a significant indirect effect of depression through emotional eating on nutritional status (p<0.001). Conclusions: Worsening depression, as indicated by higher GDS-15 scores, increases emotional eating behavior based on the DEBQ-EE and leads to poorer nutritional status among older women.